In vitro and ex vivo antiplasmodial activity of 1-(3-benzyloxy-4-methoxy-phenyl)-3-(3,4,5-trimethoxy-phenyl)-propan-1-one) against circulating strains of Plasmodium spp. in the state of Rondônia, Brazil - Vanessa Margarida Vicentini; Welington da Silva Paula do Nascimento; Marcinete Latorre Almeida; Daniel Sol Sol de Medeiros; Ana Paula de Azevedo dos Santos; Joana D 'Arc Neves Costa; Dhélio Batista Pereira; Mauro Shugiro Tada; Leonardo de Azevedo Calderon; Carolina Bioni Garcia Teles (Universidade de São Paulo, 2023)
Abstract Malaria is a disease caused by Plasmodium spp. protozoa. The ability of Plasmodium to develop resistance to current antimalarial drugs makes the study of chemotherapeutic alternatives extremely important. This study aimed to evaluate the antimalarial activity of compound 3286938 (1-(3-benzyloxy-4-methoxy-phenyl)-3-(3,4,5-trimethoxy-phenyl)-propan-1-one), which presents in its structure a 3,4,5-trimethoxyphenyl group, in vitro, using the W2 strain of P. falciparum and against circulating strains of P. vivax and P. falciparum from the state of Rondônia. The compound 3286938 obtained an IC50 of 24.4 µM against the W2 strain of P. falciparum, and against the circulating strains, it presented a median (MD)=38.7 µM for P. vivax and MD=6.7 µM for P. falciparum. As for toxicity, 3286938 showed CC50 > 500 µM for VERO and HepG2 strains with a selectivity index greater than 12.9, a ratio calculated for P. falciparum and P. vivax regarding Vero and HepG2 cells. The compound was not considered hemolytic in in vitro assays, thus indicating the specificity of its antiplasmodial action. Based on the results presented, and considering the unprecedented character of the compound, it can be concluded that 3286938 was shown to be promising for complementary in vitro and in vivo studies aiming to produce effective antiplasmodial action.